Successful mobile extracorporeal membrane oxygenator for COVID‐19 severe respiratory failure. Issue 12 (10th October 2020) - Brozzi, Nicolas; Hernandez‐Montfort, Jaime; Noguera, Edward; McWilliams, Carla; Sheffield, Cedric; Minear, Steven; Jacobs, Jeffrey; Navas, Viviana; Velez, Mauricio; Cubeddu, Robert; Navia, Jose L.
Abstract: High volume extracorporeal membrane oxygenation (ECMO) centers have developed mobile ECMO programs in recent years to facilitate the implementation of ECMO support at hospitals with lower capabilities, and transfer these patients for further care. We report a case of mobile ECMO on a patient with coronavirus disease 2019‐related acute respiratory distress syndrome, and discuss the potential application in the current severe acute respiratory syndrome coronavirus 2 pandemic.